Efficacy and safety of acupuncture for early postpartum stress urinary incontinence: A protocol for a pilot randomized controlled trial. - Yi Yang; Meng Xu; Qingguo Liu; Xiaoqing Ding; Xi Wang; Dongfeng Wang; Qisheng Sun; Xiaowei Shi; Xiuping Zhang; Dong Liu; Shufeng Shi (PLoS ONE)
Objective Postpartum stress urinary incontinence (PSUI) is a common condition among women after childbirth. While acupuncture is a common clinical treatment for PSUI, high-quality clinical evidence supporting its effectiveness is currently lacking. This study aims to preliminarily evaluate the efficacy and safety of acupuncture for early postpartum stress urinary incontinence, providing reference data for sample size calculation and protocol feasibility in formal trials. Design and methods This is a randomized controlled trial. Seventy-two PSUI patients between 42 days and 1 year postpartum will be randomly assigned in a 1:1 ratio to either the acupuncture group (n = 36) or the sham acupuncture group (n = 36). Both groups will receive acupuncture treatments three times per week for two weeks. Both groups will receive identical education regarding pelvic floor muscle training. The primary outcomes are changes in urine leakage volume measured by 1-hour pad test at week 2 of treatment and week 6 of follow-up compared to baseline (week -1), and the proportion of patients achieving at least 50% reduction in urine leakage volume at week 2 compared to baseline. Secondary outcomes include 72-hour bladder diary, The International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF), Incontinence Quality of Life questionnaire (I-QOL), and pelvic floor muscle strength assessment. Discussion The results of this study will provide preliminary evidence on the efficacy and safety of acupuncture for PSUI, offering reference data for sample size calculation and protocol feasibility in formal trials, ultimately providing more treatment options for PSUI patients. Trial registration ITMCTR2024000290.